THE USE OF ROLE PLAYS IN IMPROVING STUDENTS’ VOCABULARY MASTERY AT GRADE ELEVEN OF PERSADA SENIOR HIGH SCHOOL - Sando Formadon; Dameria Magdalena Sidabalok (Universitas Bandar Lampung, 2017)
This research aimed to know how role play in improving the students’ vocabulary mastery at SMA Persada Bandar Lampung. Role play is applied in order to persuade the students to create connection between vocabularies, understanding and the content that is studied by them. This research will use qualitative research. The researcher would understand that world from the perspective of the people in that place; add the perspective from the student opinion. The researcher would be done at grade eleven of Persada Senior High School Bandar Lampung. The data would be gathered by observing the students in the class, providing them questionnaire in the end of the researcher study. The result from combination between two instruments above was in the form of table and it was explained by some sentence that interpreted the table. The result indicated that the role play technique gave the improvement for the students especially in improving their vocabulary mastery. And their pronunciation better than before, therefore it is recommended that the students are required to improve their vocabulary as well as understanding through using role play technique. The result showed that role play technique was effective to improve the students’ vocabulary. Besides, the technique could also enhance their interest and confidence in their English study.